Internet children's television series, 1997-2015 - Terrace, Vincent, 1948- (McFarland & Company, Inc., Publishers, 2016)
"A one-of-a-kind book that chronicles television produced for the Internet. It, along with its four prior volumes is the only printed source that covers the Internet. The reader will find story lines, casts and credits, web sites, episode listings and year of production. This edition covers 573 children's series"--